Impact of blood-brain barrier integrity on tumor growth and therapy response in brain metastases - Osswald, Matthias; Blaes, Jonas; Liao, Yunxiang; Solecki, Gergely; Bergmeister-Berghoff, Anna Sophie; Wick, Wolfgang; Winkler, Frank (Clinical cancer research, 2016)
Purpose: The role of blood-brain barrier (BBB) integrity for brain tumor biology and therapy is a matter of debate. Experimental Design: We developed a new experimental approach using in vivo two-photon imaging of mouse brain metastases originating from a melanoma cell line to investigate the growth kinetics of individual tumor cells in response to systemic delivery of two PI3K/mTOR inhibitors over time, and to study the impact of microregional vascular permeability. The two drugs are closely related but differ regarding a minor chemical modification that greatly increases brain penetration of one drug. Results: Both inhibitors demonstrated a comparable inhibition of downstream targets and melanoma growth in vitro. In vivo, increased BBB permeability to sodium fluorescein was associated with accelerated growth of individual brain metastases. Melanoma metastases with permeable microvessels responded similarly to equivalent doses of both inhibitors. In contrast, metastases with an intact BBB showed an exclusive response to the brain-penetrating inhibitor. The latter was true for macro- and micrometastases, and even single dormant melanoma cells. Nuclear morphology changes and single-cell regression patterns implied that both inhibitors, if extravasated, target not only perivascular melanoma cells but also those distant to blood vessels. Conclusions: Our study provides the first direct evidence that nonpermeable brain micro- and macrometastases can effectively be targeted by a drug designed to cross the BBB. Small-molecule inhibitors with these optimized properties are promising agents in preventing or treating brain metastases in patients. Clin Cancer Res; 22(24); 6078-87. ©2016 AACR. See related commentary by Steeg et al., p. 5953